2019
DOI: 10.1142/s0219498820501650
|View full text |Cite
|
Sign up to set email alerts
|

Group gradations on Leavitt path algebras

Abstract: Given a directed graph [Formula: see text] and an associative unital ring [Formula: see text] one may define the Leavitt path algebra with coefficients in [Formula: see text], denoted by [Formula: see text]. For an arbitrary group [Formula: see text], [Formula: see text] can be viewed as a [Formula: see text]-graded ring. In this paper, we show that [Formula: see text] is always nearly epsilon-strongly [Formula: see text]-graded. We also show that if [Formula: see text] is finite, then [Formula: see text] is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Crucial to our investigation, Nystedt andÖinert have shown that a Leavitt path algebra associated to a finite directed graph is epsilon-strongly Z-graded (see [23,Thm. 1.2]).…”
Section: 3mentioning
confidence: 85%
See 2 more Smart Citations
“…Crucial to our investigation, Nystedt andÖinert have shown that a Leavitt path algebra associated to a finite directed graph is epsilon-strongly Z-graded (see [23,Thm. 1.2]).…”
Section: 3mentioning
confidence: 85%
“…However, since an epsilon-strong Z-grading is strong if and only if ǫ i = 1 for every i ∈ Z (see [23,Prop. 3.2]), it follows that the above Z-grading of M 2 (R) is not strong.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the exposed above, the importance of understanding the grading of a Leavitt path algebra is clear. In particular, the integer grading of a Leavitt path algebra has been studied in [20], where the unital Leavitt path algebras which are strongly graded are completely characterized, in [10,18], where strongly graded Leavitt path algebras are characterized in terms of Condition (Y), and in [23], where it is shown that the Leavitt path algebra associated to a finite graph is epsilon-strongly Z-graded. The grading over the free group of the edges has been introduced in [13] and has been used to give alternative proofs of interesting results, such as the Reduction Theorem and the simplicity criteria for Leavitt path algebras (see [13,16,12]) and is related to branching systems, see [6].…”
Section: Introductionmentioning
confidence: 99%
“…1.2]). Seeking to extend their result, they introduced the notion of a nearly epsilonstrongly graded ring (see Definition 2.2) and proved that every Leavitt path algebra (even for infinite graphs) is nearly epsilon-strongly Z-graded (see [17,Thm. 1.3]).…”
mentioning
confidence: 99%